Fermentation couples Chloroflexi and sulfate-reducing bacteria to Cyanobacteria in hypersaline microbial mats - Lee, Jackson Z.; Burow, Luke C.; Woebken, Dagmar; Everroad, R C.; Kubo, Michael D.; Spormann, Alfred M.; Weber, Peter K.; Pett-Ridge, Jennifer; Bebout, Brad M.; Hoehler, Tori M. (Frontiers in Microbiology, 2014)
Past studies of hydrogen cycling in hypersaline microbial mats have shown an active nighttime cycle, with production largely from Cyanobacteria and consumption from sulfate-reducing bacteria (SRB). However, the mechanisms and magnitude of hydrogen cycling have not been extensively studied. Two mats types near Guerrero Negro, Mexico -- permanently submerged Microcoleus microbial mats (GN-S), and intertidal Lyngbya microbial mats (GN-I) -- were used in microcosm diel manipulation experiments with 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU), molybdate, ammonium addition, and physical disruption to understand the processes responsible for hydrogen cycling between mat microbes. Across microcosms, H2 production occurred under dark anoxic conditions with simultaneous production of a suite of organic acids. H2 production was not significantly affected by inhibition of nitrogen fixation, but rather appears to result from constitutive fermentation of photosynthetic storage products by oxygenic phototrophs. Comparison to accumulated glycogen and to CO2 flux indicated that, in the GN-I mat, fermentation released almost all of the carbon fixed via photosynthesis during the preceding day, primarily as organic acids. Across mats, although oxygenic and anoxygenic phototrophs were detected, cyanobacterial [NiFe]-hydrogenase transcripts predominated. Molybdate inhibition experiments indicated that SRBs from a wide distribution of dsrA phylotypes were responsible for H2 consumption. Incubation with 13C-acetate and nanoSIMS (secondary ion mass-spectrometry) indicated higher uptake in both Chloroflexi and SRBs relative to other filamentous bacteria. These manipulations and diel incubations confirm that Cyanobacteria were the main fermenters in Guerrero Negro mats and that the net flux of nighttime fermentation byproducts (not only hydrogen) was largely regulated by the interplay between Cyanobacteria, SRBs, and Chloroflexi.